2013
DOI: 10.12970/2310-9971.2013.01.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and Limitations of Bile Acids in Type 2 Diabetes Mellitus: Applications of Microencapsulation as a Novel Oral Delivery System

Abstract: Type 2 diabetes (T2D) is a chronic metabolic disorder resulting from genetic and environmental factors that bring about tissue desensitization to insulin and consequent hyperglycemia. Despite strict glycemic control and the fact that new and more effective antidiabetic drugs are continuously appearing on the market, diabetic patients still suffer from the disease and its complications. Recent findings present a strong link between diabetes, inflammation, altered gut microbiota and bile acid (BA) disturbances. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…SA is a biodegradable polymer that protects the drug, and its physicochemical properties are impacted by gastrointestinal pH values [ 19 , 61 ]. The pH values examined were chosen based on previous studies conducted in our lab, which typically reflect the distal segment of the small intestine from where the absorption of the antidiabetic drug, either alone or together with bile acids, should occur [ 22 , 44 , 62 ]. The membrane-stabilising studies showed microcapsules had increased swelling properties in higher pH values for both formulations indicating that SA undergoes extensive swelling at high pH due to higher water uptake caused by increasing its porosity, water infiltration, and solubilisation of the polymer [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SA is a biodegradable polymer that protects the drug, and its physicochemical properties are impacted by gastrointestinal pH values [ 19 , 61 ]. The pH values examined were chosen based on previous studies conducted in our lab, which typically reflect the distal segment of the small intestine from where the absorption of the antidiabetic drug, either alone or together with bile acids, should occur [ 22 , 44 , 62 ]. The membrane-stabilising studies showed microcapsules had increased swelling properties in higher pH values for both formulations indicating that SA undergoes extensive swelling at high pH due to higher water uptake caused by increasing its porosity, water infiltration, and solubilisation of the polymer [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids primary function is to support solubilisation and digestion of lipids. Recently they have been shown to improve oral drug delivery as absorption and permeation-enhancing agents as well as improving drug stability [ 20 , 21 , 22 ]. The secondary bile acid lithocholic acid (LCA) has shown anti-inflammatory and formulation-stabilising effects in atherosclerosis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The VNM uses vibration, causing a breakup of laminar liquid, which, resulting from frequency selection, causes equally sized droplets where the higher the frequency, the smaller the produced microcapsules [50,98,120]. The spherical droplets are formed as a direct result of surface tension [50,120].…”
Section: Vibrational Nozzle Methodsmentioning
confidence: 99%
“…The VNM uses vibration, causing a breakup of laminar liquid, which, resulting from frequency selection, causes equally sized droplets where the higher the frequency, the smaller the produced microcapsules [50,98,120]. The spherical droplets are formed as a direct result of surface tension [50,120]. The VNM technique also utilises a range of other parameters aside from vibration frequency, including nozzle size, electrode tension and jet flow rate to result in droplet formation [96,98,[121][122][123][124].…”
Section: Vibrational Nozzle Methodsmentioning
confidence: 99%
See 1 more Smart Citation